The use of polyurethane for asphalt pavement engineering applications: A state-of-the-art review. (20th November 2019) - Cong, Lin; Yang, Fan; Guo, Guihong; Ren, Minda; Shi, Jiachen; Tan, Le
Highlights: The relationship between structure and properties of polyurethane is introduced. Polyurethane modified asphalt has good compatibility and high-temperature stability. The application of polyurethane in asphalt pavement maintenance is presented. The polyurethane mixture has excellent properties and is suitable for functional pavement applications. The application of polyurethane waste in asphalt pavement is a new research field of its recycling. Abstract: Asphalt pavement often suffers from rutting, aging, cracks, and pits during the life cycle. Although traditional polymer modifiers can improve asphalt properties to some extent, its storage stability and aging resistance still need to be improved. Polyurethane (PU) has been used in asphalt pavement engineering because of its high mechanical properties, durability and fatigue resistance. This paper introduces the relationship between the structure and properties of PU and describes possible optimization of the raw materials of PU suitable for modified asphalt according to the pavement performance. The applications of PU in modified asphalt, pavement maintenance, foamed asphalt, and its mixture are reviewed. The results show that modified with PU asphalt has good deformation resistance, aging resistance, fatigue resistance, and high-temperature storage properties after physical and chemical modification. At the same time, PU can also improve the temperature stability and mechanical properties of emulsified asphalt. The PU mixture has excellent properties and can be used to prepare functional pavement such as water penetration, noise reduction, and anti-skidding. The application of PU waste materials in asphalt pavement opens up a new direction for its recycling.